2022
DOI: 10.3389/fnut.2022.867745
|View full text |Cite
|
Sign up to set email alerts
|

EVOO Promotes a Less Atherogenic Profile Than Sunflower Oil in Smooth Muscle Cells Through the Extracellular Vesicles Secreted by Endothelial Cells

Abstract: BackgroundLittle is known about the effect of extra virgin olive (EVOO) and sunflower oil (SO) on the composition of extracellular vesicles (EVs) secreted by endothelial cells and the effects of these EVs on smooth muscle cells (SMCs). These cells play an important role in the development of atherosclerosis.MethodsWe evaluated the effects of endothelial cells-derived EVs incubated with triglyceride-rich lipoproteins obtained after a high-fat meal with EVOO (EVOO-EVs) and SO (SO-EVs), on the transcriptomic prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…MiR-19b encapsulated in HUVECs-EVs mentioned above ( 52 ), the previous name of miR-19b-3p, reduced HUVECs migration and damaged lymphatic system function by negatively regulating TGF-βRII expression ( 56 , 76 ). MiR-19b-3p in endothelial microparticles (MPs) exaggerated AS by targeting the suppressor of cytokine signaling 3 (SOCS3) ( 77 ).…”
Section: The Flexibility and Versatility Of Mirnas Encapsulated In Ec...mentioning
confidence: 94%
See 3 more Smart Citations
“…MiR-19b encapsulated in HUVECs-EVs mentioned above ( 52 ), the previous name of miR-19b-3p, reduced HUVECs migration and damaged lymphatic system function by negatively regulating TGF-βRII expression ( 56 , 76 ). MiR-19b-3p in endothelial microparticles (MPs) exaggerated AS by targeting the suppressor of cytokine signaling 3 (SOCS3) ( 77 ).…”
Section: The Flexibility and Versatility Of Mirnas Encapsulated In Ec...mentioning
confidence: 94%
“…Xiang et al ( 51 ) performed miRNA-Seq analysis and found that EVs derived from lipopolysaccharide (LPS)-stimulated human umbilical vein endothelial cells (HUVECs) promoted human aortic smooth muscle cell (HASMC) proliferation and migration, in which four upregulated miRNAs (including miR-27a-3p, miR-126-5p, miR-155-5p, and miR-365b-3p) and nine downregulated miRNAs (including let-7b-5p, miR-10a-5p, miR-10b-5p, miR-21-3p, miR-30a-5p, miR-92a-3p, miR-125a-3p, miR-143-3p, and miR-181a-2-3p) participated in various aspects of atherosclerotic lesion formation. In another RNA-seq research, a significant upregulation of 49 miRNAs (including miR-19b-3p and miR-126-5p) and downregulation of 19 miRNAs in extra-virgin olive-induced HUVECs-EVs compared to sunflower oil-induced HUVECs-EVs were observed, which closely linked to the development of AS ( 52 ). The finding of higher expression of miR-126-5p was detected in both studies ( 51 , 52 ).…”
Section: The Flexibility and Versatility Of Mirnas Encapsulated In Ec...mentioning
confidence: 97%
See 2 more Smart Citations